Evaluation of Endogenous Sugars, Chlorogenic Acid and Caffeine Associated with Direct Somatic Embryogenesis of Coffee (Coffea arabica L.) - Isutsa, D. K.; Mayoli, R. N.; Nyende, A. B.; Mweu, C. M. (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
Coffee is one of the most important cash crops cultivated in the world with great economic importance. During the induction of somatic embryogenesis, there are different endogenous compounds involved in the success or failure of the somatic embryogenesis response and these compounds determine the specificity of cellular responses. This present experiment identified and quantified endogenous sugars, chlorogenic acid and caffeine present during somatic embryogenesis of ‘Ruiru 11’. Laboratory experiments were set up at Coffee Research Institute, Ruiru-Kenya between 2014 and 2016. Third leaf pair explants were excised from 8-monthold greenhouse-grown mother plants and cultured in half strength Murashige and Skoog basal salts augmented with Thidiazuron. Once embryos had developed, the cultures were analysed for endogenous sugars, caffeine and chlorogenic acid using HPLC. Generally, green embryogenic cultures contained more and higher quantities of the compounds. Glucose and fructose were highest (38.95 mg/g and 45.43 mg/g respectively) in leaf discs of brown non-embryogenic cultures. Sucrose was highest (62.15 mg/g) in embryos of green embryogenic cultures. Embryos of green embryogenic cultures had the highest chlorogenic acid (5.3 mg/g), whereas caffeine was highest (0.55 mg/g) in embryos of brown embryogenic cultures. Endogenous fructose and glucose inhibited embryogenesis, while sucrose, chlorogenic acids and caffeine promoted embryogenesis and are potential biomarkers for embryogenesis. Other biochemical compounds such as organic acids should be identified and their role in coffee somatic embryogenesis determined.